C-Reactive Protein/Albumin Ratio as an Independent Predictor of Mortality in Critically Ill Pediatric Patients - Mohamed, Shereen A.; ElHawary, Rabab (Journal of Child Science, 2020)
It is necessary to stratify the risk of pediatric patients at the time of intensive care unit (ICU) admission and to predict their outcomes. This helps to allocate the scarce ICU resources to start the appropriate treatment. The objective of this study was to evaluate the prognostic value of C-reactive protein/albumin ratio on admission to pediatric intensive care unit (PICU) in predicting mortality, PICU length of stay, the need for mechanical ventilation, and the use of inotropic drugs. This cohort study was conducted at Pediatric Cairo University Hospital. The study included 178 critically ill children. Pediatric Risk of Mortality–III (PRISM-III) score was calculated; CRP and serum albumin levels were assessed within 24 hours from admission. The median CRP/albumin ratio was significantly higher in nonsurvivors than survivors (18.60 and 4.65, respectively). The CRP/albumin ratio at a cutoff of ≥25.83 had significant discriminatory power in predicting mortality (area under the curve [AUC] = 0.795 and p < 0.001) with 85.4% accuracy. Furthermore, CRP/albumin ratio alone showed a comparable discriminatory power to that of PRISM-III score (AUCs = 0.795 and 0.793, respectively). A multivariable logistic regression analysis revealed that each unit of increase in the CRP/albumin ratio increased the risk of mortality by 1.075 (odds ratio [OR] = 1.075). CRP/albumin ratio showed a significantly higher median in ventilated (6.86) compared with non-ventilated (5.22) patients. Patients supported with inotropes showed significantly higher median CRP/albumin ratio (11.70 and 3.68, respectively). CRP/albumin ratio at admission to PICU was a good independent predictor of mortality.
Keywords: C-reactive protein/albumin ratio; hypoalbuminemia; intensive care units; mortality; outcomes; pediatric